Pemanfaatan Ampas Kulit Pisang dan Kulit Jeruk Sebagai Pupuk Kompos: Meningkatkan Kesuburan Tanah, Pertumbuhan Tanaman, dan Keberlanjutan LingkunganPemanfaatan Ampas Kulit Pisang dan Kulit Jeruk Sebagai Pupuk Kompos: Meningkatkan Kesuburan Tanah, Pertumbu - Halal, Andi Hartina (Unri Conference Series: Community Engagement, 2024)
The utilization of banana peel waste as compost is motivated by the large number of bananas consumed by the community, precisely in Tompong Patu Village in various kinds of processed foods, including processed as fried bananas which are in great demand by the community, so that it can produce quite a lot of waste. However, this problem has not been fully realized by the community, especially the partners of the Tompong Patu Village Family Hope Group. This is due to the low ability and understanding of partners, both waste processing and the impact of waste. Therefore, this community service program will help partners in overcoming waste problems by processing banana peel and skin waste into compost. The implementation method in this community service is carried out by following three stages, namely Socialization, Training and Assistance. The results obtained are in the form of increased knowledge and skills of partners in processing banana peel and orange peel waste into compost, so that this compost product can be used as a village superior product, especially in Tompong Village, Tompong Patu Hamlet.